ChemInform Abstract: Synthesis of Ynone Trifluoroborates Toward Functionalized Pyrazoles. Issue 10 (7th March 2013) - Kirkham, James D.; Edeson, Steven J.; Stokes, Stephen; Harrity, Joseph P. A.
Abstract Coupling of novel ynone trifluoroborates like (III) with hydrazines provides a new, efficient, and regioselective approach to pyrazole trifluoroborates as precursors of diverse pyrazole derivatives.